2022
DOI: 10.1117/1.jmi.9.1.013501
|View full text |Cite
|
Sign up to set email alerts
|

Compton coincidence in silicon photon-counting CT detectors

Abstract: Purpose: Compton interactions amount to a significant fraction of the registered counts in a silicon detector. In a Compton interaction, only a part of the photon energy is deposited and a single incident photon can result in multiple counts unless tungsten shielding is used. Deep silicon has proved to be a competitive material for photon-counting CT detectors, but to improve the performance further, one possibility is to use coincidence techniques to identify Compton-scattered photons and reconstruct their in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(38 reference statements)
0
11
0
Order By: Relevance
“…Since the bias voltage affects the electric field in the detector, increasing the bias voltage reduces the time required for the charge carriers to be collected. In this work, a bias voltage of 200 V was used in alignment with our previous publications 8 , 9 . However, this is not necessarily the optimum for maximizing the performance of estimating the time of each pulse.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since the bias voltage affects the electric field in the detector, increasing the bias voltage reduces the time required for the charge carriers to be collected. In this work, a bias voltage of 200 V was used in alignment with our previous publications 8 , 9 . However, this is not necessarily the optimum for maximizing the performance of estimating the time of each pulse.…”
Section: Discussionmentioning
confidence: 99%
“…The required timing resolution to resolve the interactions corresponding to a single incident photon was estimated in our previous work regarding Compton coincidence detection 8 . Based on a 25×25 mm2 detector area as seen from the x-ray source, it was concluded that a time window of 1 ps was required given an incident photon flux of 340 Mcps/mm2, corresponding to the maximum CT flux in an intermediate-sized chest image 26 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations